2012
DOI: 10.1007/s00464-012-2235-2
|View full text |Cite
|
Sign up to set email alerts
|

Totally laparoscopic strategies for the management of colorectal cancer with synchronous liver metastasis

Abstract: Totally laparoscopic strategies for the radical treatment of stage IV colorectal cancer are feasible with low morbidity and favorable outcomes. A laparoscopic approach for the simultaneous management of SCRLM and primary colon cancer is associated with reduced surgical access trauma, postoperative morbidity, and hospital stay with no compromise in short-term oncological outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 41 publications
0
43
2
3
Order By: Relevance
“…Another option is to combine laparoscopic colorectal surgery with percutaneous radio frequency. This tactic was reported by Polignano et al [20]. with excellent short-term results and no compromise in oncological outcome.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another option is to combine laparoscopic colorectal surgery with percutaneous radio frequency. This tactic was reported by Polignano et al [20]. with excellent short-term results and no compromise in oncological outcome.…”
Section: Discussionmentioning
confidence: 85%
“…Several teams have reported the feasibility of simultaneous resection of both primary CRC and SCRLM [20][21][22][23]. However, few studies had compared patients who underwent combined resections by either open or laparoscopic approach [22,[24][25][26].…”
Section: Resultsmentioning
confidence: 99%
“…This reflects the contemporary trend of an increase in the number of studies reporting laparoscopic liver resections performed for malignant lesions. 5,11,17,19 A recent meta-analysis of 15 studies with long-term oncologic outcomes showed that laparoscopic liver resections resulted in equivalent survival One postoperative death (within 90 d) occurred in our study; the patient died of liver failure from underlying steatohepatitis, not the operation itself. The rate of postoperative complications reported in the literature varies among studies, with lower rates reported in series with predominantly minor resections 8,12 and higher rates reported in series with predominantly major resections.…”
Section: Discussionmentioning
confidence: 50%
“…The indications for laparoscopic liver resection in early reports were limited to benign lesions, and over the last decade there has been growing experience with adopting laparoscopic liver resection for primary and metastatic lesions. [17][18][19] The present study demonstrates that within 3 years of introducing laparoscopic liver resection to an HPB surgeon's practice in a Canadian HPB centre of excellence, one can achieve a median decrease in duration of surgery of 67 minutes despite a more than 2-fold increase in malignant caseload while maintaining perioperative outcomes comparable to those at other experienced centres.…”
Section: Discussionmentioning
confidence: 56%
“…As described in other studies evaluating the risks of mortality after colorectal surgery (7,8), we have used the age of 70 years as our cut-off to define "elderly" patients.…”
Section: Methodsmentioning
confidence: 99%